Idealisme Syofyani Terhadap Gaya Tari Berdampak Pada Popularitas Keseniannya - Anugrah Prima Insani; Indrayuda Indrayuda; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2020)
AbstractThis article aims to reveal and explain Syofyani's idealism againsts dance style that has an impact on its popularity in the community. This type of research was qualitative with using descriptive method. The research instrument was the researcher as a key instrument, and it was assisted by both audio and visual recording devices. Location of the research was in Padang city. The informants were dance performers, choreographers and managers of studios and user communities. Data were collected by taking observation, interview, documentation study and literature study. Data analyses were done by referring to the Miles and Huberman technique, namely the stages of collecting, reducting, presenting, verificating and making conclusion of data. The results of the research show Syofyani's idealism regarding her style such as dance attitude, dance motions motive, motions rhythm, movement characters and expressions, distinguishing the dance styles created by Syofyani with dance works from other choreographers. Besides that, Syofyani's idea about her dance style is departing from the Minangkabau concept of women and men, as well as about Minangkabau customs towards the position of women and men who naturally changed. By looking at this distinctive dance style, Syofyani has become popular among the dance lovers community in West Sumatra.